Divergent flow isoelectric focusing: fast and efficient method for protein sample preparation for mass spectrometry - Mazanec, Karel; Bobalova, Janette; Slais, Karel (Analytical and bioanalytical chemistry, 2009)
A study of complex protein mixtures obtained from biological samples by MS demands proper purification and separation technique. The method of divergent flow isoelectric focusing (DF IEF) promises improvement of sample preparation in proteomic studies. DF IEF was carried out in a separation channel with increasing width. The channel was cut out from a polyester nonwoven web. DC voltage (800 V) was brought to two pairs of electrodes situated on the channel sides. Amphoteric compounds, including proteins, drift through the channel carried by flow (18-25 ml/h) in streamlines given by their isoelectric points. The pH gradient (3-10) and its stability during analysis have been monitored with colored low-molecular mass pI markers. Separated fractions were collected in ten microvials and further analyzed by MS. The suggested method was used for separation and purification of crude protein extract from barley grain, malt, and beer. Collected fractions of separated proteins were characterized by MALDI-MS. Desalting during IEF enhanced significantly the quality of mass spectra. It also simplified monitoring of post-translational modifications and protein changes occurring during malting and brewing. Results have shown the real potential of the suggested DF IEF device lay-out as an efficient preparative tool for separation and purification of complex protein mixtures for further analyses.
Keywords: Equipment Design; isoelektrická fokusace; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Hydrogen-Ion Concentration; Reproducibility of Results; Time Factors; časové faktory; proteomika; Sensitivity and Specificity; senzitivita a specificita; Proteins; Proteomics; reprodukovatelnost výsledků; proteiny; Electrodes; molekulová hmotnost; Isoelectric Focusing; elektrody; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Molecular Weight; design vybavení; koncentrace vodíkových iontů; Analytic Sample Preparation Methods; metody pro přípravu analytických vzorků